Participatory research to develop and design the brand and package for community's food products: Case study salted eggs products of Hin Khao Village, Ban Tak District, Tak Province - รัติภัทร์, ซินเนีย; คุ้มญาติ, ปิยะวรรณ (RMUTL Journal of Business Administration and Liberal Arts, 2018)
The current business environment is more competition, especially consumer goods. This paper seeks and investigate the importance of branding and packaging for salted eggs products in Hin Khao Village by focusing on studying problems and requirements of branding and packaging. In order to get the data to develop branding and packaging style. And finish with the stakeholders' satisfaction evaluate on branding and packaging style of salted egg products. The researchers used a participatory research method which learning and sharing process including researchers, leaders, and members of the community. And using empirical examination from survey data of customer, manufacturers, and government representative to analyze the least squares regression. This analysis investigates the relationship between the variables on the seven assumptions and using median for the satisfaction measurement of the brand and packaging that are designed and developed. The research found that, the packaging type 2 that was developed on symbolic elements, form, color, and font style have a positive effect on customer satisfaction. Moreover, the packaging type 3 that was designed and developed with respect to the components of product protection has a positive effect on customer satisfaction. Furthermore, the packaging type 1 through 3 that was designed and developed with respect to the components of product identity has a positive effect on customer satisfaction. Finally, from the mean comparing of brand satisfaction, we found that the respondents were satisfied with the new brand model rather than the original model. The packaging design that has a highest mean customer satisfaction is the packaging type 4. This article provides findings on the branding and packaging development with the new changes, which the theoretical discussion, adoption, and suggestions for future research